The effects of polio eradication efforts on health systems: A cross-country analysis using the Develop–Distort Dilemma - Rodriguez, Daniela C; Neel, Abigail H; Mahendradhata, Yodi; Deressa, Wakgari; Owoaje, Eme; Akinyemi, Oluwaseun; Sarker, Malabika; Mafuta, Eric; Gupta, Shiv D; Salehi, Ahmad Shah; Jain, Anika; Alonge, Olakunle (Oxford Academic, 2022)
This article was published in Health Policy and Planning by Oxford Academic [© The Author(s) 2021. Published by Oxford University Press in association with The London School of Hygiene and Tropical Medicine.] and the definite version is available at: https://doi.org/10.1093/heapol/czab044 The Journal's website is at: https://academic.oup.com/heapol/article/36/5/707/6244781